Meaning of "Bersih.Desa" at the Bangun Harjo Village, Bataguh Subdistrict, Kapuas District. - Kusumawati, Trivina (JURNAL SOCIUS, 2023)
Bersih desa is a hereditary ritual that is carried out every once a year, as an expression of respect and thanks for what has been received and given.The purpose of this study was to find out (1) the background of the implementation of the village clean tradition (2) the implementation of the village clean ceremony (3) symbol changes that occurred (4) the meaning contained in the implementation of clean villages in the community in Bangun Harjo Village, Bataguh District, Kapuas Regency.The study uses qualitative research methods with a phenomenological approach. The sampling technique used is purposive sampling. White the techniques in collecting data are used by means of observation, interviews and documentation.The results of the research obtained in the field indicate that : (1) the background of the holding of this village’s clean tradition is to preserve a tradition from generation to generation for the younger generation. (2) this clean village implemented in the village of Bangun Harjo has a sense of kinship and solidarity among its very high citizens. (3) symbol changes that occur in the form of these objects are from wrapping paper side dishes to become a place for rice (ceting), entertainment used to be still traditional now has begun to be modern. (4) for community members in Bangun Harjo Village, Bataguh District, Kapuas District, the meaning of the village clean tradition reveals gratituee to the Almighty God for everything that has been given to the community, such as health and safety and the sustenance that has been gained.